How strenuous is esports? Perceived physical exertion and physical state during competitive video gaming - Tholl, Chuck; Soffner, Markus; Froböse, Ingo (Frontiers in Sports and Active Living, 2024)
Introduction: Esports or competitive video gaming is a rapidly growing sector and an integral part of today's (youth) culture. Esports athletes are exposed to a variety of burdens, that can potentially impact an athlete's health and performance. Therefore, it is important that esports athletes are aware of (physical) burden and exertion associated with esports. For this purpose, a study was conducted to evaluate the influence of competitive video gaming on the perceived physical exertion and the perceived physical state (PEPS).Methods: Thirty-two healthy male esports athletes participated in two competitive video gaming sessions lasting 90-120 minutes, interrupted by a 10-minute passive sitting break. Repeated measures of perceived physical exertion (Borg Categorial Ratio-10 scale) and perceived physical state were recorded before, during, and after each video game session. Repeated measures ANOVA and Friedman's test were used for statistical analysis.The results showed a significant difference in all dimensions of the PEPS (p < 0.05) as well as in Borg scale (p < 0.001). Post-hoc tests revealed significant increases in Borg scale between baseline measurements (T0: 1.0 ± 1.0) and after the first competitive video gaming session (T1: 2.4 ± 1.3, p < 0.001), as well as after the second competitive video gaming session (T3: 3.0 ± 1.7, p < 0.001). Furthermore, there was a significant reduction in perceived exertion between the measurement time after the first competitive video gaming session (T1) and the break (T2: 1.3 ± 1.2, p < 0.001). The PEPS dimensions activation, trained, and mobility showed similar significant changes in post-hoc analysis.The results indicate that the perceived physical burden significantly increases during esports participation. As the duration of competitive video gaming extends, the perceived physical state decreases and perceived physical exertion increases. A passive break between two video game sessions can at least partially restore physical exertion and physical state. However, this break neither returns the scores to their baseline levels nor prevents a further decline in scores during the second video game session. Over time and with a lack of observation, this could result in health and performance limitations.